Study of tensile properties for aluminum 6061 reinforced with AISI 1060 steel machining chips - Samiran, N. A.; Mohamad Rus, M. A.; Mat Hassan, N. N.; Ishak, M. Z.; Ishak, I. A. (Penerbit UTHM, 2021)
The present study focuses on the tensile properties of Aluminum 6061 reinforced with AISI1060 Steel machining chips. Three different types of samples of aluminium 6061 reinforced with AISI 1060 steel machining chips were prepared using stir casting. The tensile test was conducted using universal test machine (UTM) for fabricated composites to study the tensile properties of aluminium 6061 reinforced with steel machining chips AISI 1060.The samples were prepared with different composition of AISI 1060 steel machining chip of 5%, 10% and 15% according to the weight fraction of parameter variable. Two casting processes were applied in this project namely stir casting and sand casting process. The stir casting was used to mix the two different metals to become a composite at temperature between 750℃ to 800℃ in a furnace while sand casting was used to fabricate the samples into ASTM-E8M standard for tensile testing. The results showed that the samples with higher reinforcement percentages of steel machining (15%) showed higher tensile stress and higher modulus value characteristic compared to other samples. The experiment proved that the reinforcement material has good mechanical properties compared to the pure material.